2021
DOI: 10.1097/jsm.0000000000000927
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity as a Risk Factor for Sport Injury in Youth: A Systematic Review

Abstract: Objective: To determine whether high or low adiposity is associated with youth sport-related injury. Data Sources: Ten electronic databases were searched to identify prospective studies examining the association between adiposity [body mass index (BMI) or body fat] and a future time-loss or medical attention sport-related musculoskeletal injury or concussion in youth aged 20 years and younger. Two independent raters assessed the quality (Downs and Black criteria) and risk of bias (Joanna Briggs Institute Criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Qualitative systematic/scoping reviews have explored common barriers to physical activity, indicating that children with obesity may be turned off activity by a range of ‘physical factors’ [ 12 , 30 ]. Injury has been identified as a barrier to activity [ 12 , 30 ] and a new meta-analysis of prospective evidence shows that youth with a higher BMI may be at a greater risk of injuring themselves during sport (OR 1.18) [ 31 ]. In addition, children with obesity have a higher risk of fractures [ 32 ].…”
Section: How Might Neuromusculoskeletal Impairments and Complications Affect The Life Of The Child?mentioning
confidence: 99%
“…Qualitative systematic/scoping reviews have explored common barriers to physical activity, indicating that children with obesity may be turned off activity by a range of ‘physical factors’ [ 12 , 30 ]. Injury has been identified as a barrier to activity [ 12 , 30 ] and a new meta-analysis of prospective evidence shows that youth with a higher BMI may be at a greater risk of injuring themselves during sport (OR 1.18) [ 31 ]. In addition, children with obesity have a higher risk of fractures [ 32 ].…”
Section: How Might Neuromusculoskeletal Impairments and Complications Affect The Life Of The Child?mentioning
confidence: 99%
“…Considering other risk factors for BSI, a 2022 systematic review and meta-analysis of 17 prospective observational studies examined the relationship between adiposity and sports injury risk in young athletes, including BSIs [ 37 ]. Young athletes with a BSI were more likely to have a lower BMI than uninjured peers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, impaired neuromuscular and postural control has been confirmed in obese children [25], often accompanied by altered biomechanical loadings of weight-bearing skeletal tissue and an increase in systemic inflammation caused by excess adipose [26]. In general, the most recent systematic review with a meta-analysis showed that of 38 articles studied, 16 identified high adiposity as a significant risk factor for lower-extremity injury [27]. Our results demonstrate that low maternal body mass index has a protective role for sports injuries, which is not in line with the findings in the literature [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the most recent systematic review with a meta-analysis showed that of 38 articles studied, 16 identified high adiposity as a significant risk factor for lower-extremity injury [27]. Our results demonstrate that low maternal body mass index has a protective role for sports injuries, which is not in line with the findings in the literature [27,28]. A low body mass index may lead to a higher incidence of bone stress injuries among young female athletes who have a body mass index < 21 kg/m 2 , participate in physical activity ≥ 12 h/week, and have oligomenorrhea/amenorrhea [28].…”
Section: Discussionmentioning
confidence: 99%